PROBLEMS OF PRESERVATION AND FORMATION OF KHANAKA OF UZBEKISTAN (Academia Science Repository, 2023)
This article examines the role and place of the Sufi khanaka in the architecture of Uzbekistan and the effective preservation of these architectural monuments.